Metamodel-Based Multidisciplinary Design Optimization of a Deep-Sea Manganese Nodules Test Miner - Minuk Lee; Su-gil Cho; Jong-Su Choi; Hyung-Woo Kim; Sup Hong; Tae Hee Lee (Journal of Applied Mathematics)
A deep-sea manganese nodules test miner has not only coupled relationship between system components but also various design requirements of each system to meet the specified multitasks. To accomplish the multiobjectives of complex systems, multidisciplinary design optimization (MDO) is performed. Metamodels such as the kriging model and the response surface model are employed to reduce computational costs for MDO and to integrate component systems in a design framework. After verifying the accuracy of each metamodel, metamodel-based MDO for a deep-ocean test miner is formulated and performed. Finally, results and advantages of the proposed design methodology are discussed.